The Madrilenian Poetry in the Early 20th Century. Spanish > English Translated Poems of Antonio Casero (1874-1936) - Godoy Tena, Francisco (International Journal of Linguistics, Literature and Translation, 2025)
The literature in Madrid has had many masterpieces in poems, plays and novels that have remained unknown for a long time. One of the most interesting authors of Madrid’s early 20th-century literature is Antonio Casero. He belongs to one of the classical periods of the Madrilenian literature that is framed as part of a regional movement in culture, named as ‘Madrileñismo’ that had its ‘Golden Age’ between the late 19th and early 20th century. The aim of this study is to analyse, for the first time, a corpus of poems, full of Madrilenian terminology, taken from Antonio Casero’s poetical works and to make a proposal of translations from Spanish and its Madrilenian speech into English. Additionally, this research will provide some translated fragments from his poems and some translation comments. Thanks to this, they will be examples of Madrid as models to understand this rich, yet unknown, period of the Madrilenian literature within its Spanish and European contexts.